PERILAKU LENTUR PELAT LANTAI SEMI-PRECAST MENGGUNAKAN SHEAR CONNECTOR PADA DAERAH LAPANGAN (TINJAUAN SAMPAI DENGAN 3 PANEL) - , feny gema pertiwi; , Ir. Suprapto Siswosukarto, Ph.D, ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Floor in storey houses is generally made by cast-in situ method using the scaffolding and bekisting. in order to reduce the use of scaffolding and bekisting material, one of the alternatives introduced to the people is the semi precast system (in the form of plate panels) combined with cast in situ system known as the composite system. The objective of this research is to identify the characteristics of semi precast composite floor using the shear connector at the interface in the field area. This research was carried out for two groups of floor plate in 1:1 scale. Each group consisted of three specimens. The first group was made in monolit and acted as the controlling specimen. The second was made in two parts: precast plate with cast in situ concrete casted on above. Each specimens were given with repeated center static load and the experiment was carried out in two steps. In the first step, the specimen was given with repeated load up to reach 30 % of the ultimate load (failure) in 20 times (cycles). In the second step, the specimen was given with load started from zero up to reach the ultimate/collapse Results of the experiment showed the comparison of PM and PK when the first crack and ultimate. The increase of plate panels was also proportional to the carrying capacity of the plate both when the first crack and ultimate. A quite significant increase ocurred in composite plate where the increase carrying capacity of PK 200 to PM 400 was from 125,25 % to 147,53 % when the first crack and from 122,46 % to 235,63 % when ultimate. The same was also occurred in PK 400 to PK 600, which was from 147,53 % to 449,58 % when the first crack and from 235,63 % to 345,85 % when ultimate The crack occurred in all plate specimens and categorized as flexural crack and the type of the collapse was flexural collapse .